Rancang Bangun Sistem Pengkonversi Mata Kuliah Mahasiswa Pindahan/Lanjutan Prodi Sistem Informasi - Ameylia Dina Hanifa; Irwansyah, Irwansyah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
The conversion of transfer student courses aims to make the education program that has previously been taken can be applied to continuing education programs, so that there is no repetition of the same education program. The problem that occurs in the Information Systems study program, Bina Darma University is that the caprodi must input one by one from the student transcript data for each conversion process, which takes a long time. Efforts to deal with these problems designed a course conversion system with a development method (System Development Life Cycle) with a waterfall model. After analyzing, it produces a design to build a course conversion system that is more effective and efficient for transfer students. This system design has a page display consisting of a dashboard page or main page, a page for processing student data, transcript data, course data starting from adding, editing, and deleting data. As well as the display that is the core of this system design, namely the conversion process page and course conversion results.